Young male with cardio-vascular complication: culprit Takayasu arteritis - Shukla, Devarshi Bharat; Akholkar, Pankaj Jasabhai; Jani, Parth Rajendrabhai; Jalawala, Neel Kiran (International Journal of Advances in Medicine, 2023)
Takayasu arteritis (TA), a rare type of granulomatous vasculitis characterized by inflammatory changes and stenosis in large and medium sized arteries with a strong predilection for the aortic arch and its branches, usually presented in young female. We are reporting a rare case of TA in 23-year-old male with cardiovascular complication in form of heart failure and hypertension with involvement of right supraclavicular artery and abdominal aorta in form of aneurysm and stenosis, respectively.